Terrestrial medium and large-sized mammalâ€™s diversity and activity patterns from Tamá National Natural Park and buffer zone, Colombia - Caceres-Martínez, Carlos Herney; Acevedo Rincón, Aldemar Alberto; González-Maya, José Fernando (THERYA, 2016)
The eastern mountain range of Andes in Colombia is one of the least studied areas for mammals in the country, yet, potentially one of the most diverse. Here we present the first survey of medium and large-sized mammals for Tamá National Natural Park (NNP) and La Carpa and La Rochela buffer areas, as basic information for the conservation and management of the NNP, including the potential inclusion of these buffer zones as part of the NNP. We used different complementary survey techniques (i. e., camera-traps, transects and interviews) to assess the diversity of these mammals in a 216 km2 area of the park; our effort included 72 linear transects of 1.8 Km, opportunistic sampling sessions, 16,714 camera trap-days, 39 structured interviews and indirect records and direct observation of animals. We recorded 21 species of mammals classified in 8 orders and 16 families distributed in four conservation categories. Complementary methods significantly improved the results. We found a dominant nocturnal activity pattern for the assemblage and low activity overlapping among most species. This is the first assessment of medium and large-sized mammalâ€™s diversity for Tamá NNP and for most North-eastern Andes in the country. Our results highlight the presence of large threatened species such as Tremarctos ornatus, Puma concolor and Mazama rufina. Our results could serve as basis for the conservation planning and management of the protected area and its buffer zones, and the potential expansion of the park.